2020
DOI: 10.3989/scimar.04993.11a
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress biomarkers in the gills of the bivalve <em>Mactra stultorum</em> exposed to acrylamide

Abstract: Acrylamide (ACR) is among the most deleterious pollutants in the environment and presents a serious risk to humans and ecosystems. The purpose of this study was to assess its effects when administered at different concentrations (5, 10 and 20 mg L–1) to evaluate antioxidant status in the gills of Mactra stultorum. Our results showed, after five days of treat­ment, an increase in malondialdehyde (MDA), lipid hydroperoxides (LOOH), advanced oxidation protein products (AOPP), reduced glutathione (GSH), ascorbic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Such findings agreed with our previous reports conducted on ACR-treated bivalves. 12,13 A wide range of cellular effects occuring due to lipid peroxidation may alter the membrane fatty acids (FAs) composition. Since FAs play a key role in organisms' metabolism, variations in their profiles are recently considered as one of the efficient tools to assess xenobiotics impact on several aquatic organisms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such findings agreed with our previous reports conducted on ACR-treated bivalves. 12,13 A wide range of cellular effects occuring due to lipid peroxidation may alter the membrane fatty acids (FAs) composition. Since FAs play a key role in organisms' metabolism, variations in their profiles are recently considered as one of the efficient tools to assess xenobiotics impact on several aquatic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…It may cause various toxicity in fish models 10 . Recent studies have revealed that ACR exerts its toxic effects on aquatic organisms by inducing oxidative stress through excessive production of reactive oxygen species (ROS) 11–13 . Biological membranes are selectively permeable barriers enclosing cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations